2010
DOI: 10.1375/twin.13.5.501
|View full text |Cite
|
Sign up to set email alerts
|

Twin Pregnancies Complicated by a Single Malformed Fetus: Chorionicity, Outcome and Management

Abstract: T he objective of this study was to evaluate the impact of one abnormal fetus in a twin pregnancy, to compare impact of chorionicity and clinical outcome of intervention and expectant management. Thirty-seven dichorionic (DC) twins and 18 monochorionic (MC) twins complicated with one malformed fetus were evaluated for gestational age, birthweight and perinatal outcome. Six hundred and forty-two twin pregnancies were evaluated in the database. The control groups consisted of 429 DC and 86 MC twins without anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Chromosomal anomalies like trisomy 21 and 18 are associated with increased risks of miscarriage, fetal growth restriction, preterm delivery and fetal demise in multiple pregnancies . In anencephalic twins, when treated conservatively, there is a 50% risk of developing polyhydramnios, which can result in preterm labor and preterm delivery . A review that compared expectant management with SF showed significantly longer gestation periods and a higher birth weight in the SF group …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromosomal anomalies like trisomy 21 and 18 are associated with increased risks of miscarriage, fetal growth restriction, preterm delivery and fetal demise in multiple pregnancies . In anencephalic twins, when treated conservatively, there is a 50% risk of developing polyhydramnios, which can result in preterm labor and preterm delivery . A review that compared expectant management with SF showed significantly longer gestation periods and a higher birth weight in the SF group …”
Section: Discussionmentioning
confidence: 99%
“…In twin pregnancies discordant for genetic or congenital anomalies such as major anatomical malformation or chromosomal anomaly, in nearly 85% of cases, the anomaly is confined to one fetus, and the co‐twin is normal . There are some circumstances, however, in which the genetic or congenital anomaly present in the affected twin can be potentially threatening to the healthy co‐twin . Anencephaly, with the potential for polyhydramnios and subsequent preterm delivery, is the most common situation in which selective feticide (SF) is indicated for the management of a congenital anomaly .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Best and Rankin reported that the risk of developing CHD is increased by 172% for MC twins and by 49% for DC twins compared with singletons. The anomalies are frequently complex, and they are often associated with poor perinatal outcomes …”
Section: Discussionmentioning
confidence: 99%
“…The anomalies are frequently complex, and they are often associated with poor perinatal outcomes. 19,20 In this cohort, there was a differential distribution of cardiovascular anomalies in MCDA and DCDA groups. Primary structural defects such as VSD/AVSD, TOF, and UIH/SA were more common in DCDA group than those in MCDA group.…”
Section: Discussionmentioning
confidence: 99%